Cost-effectiveness analysis of pembrolizumab vs. chemotherapy as second-line treatment for advanced esophageal carcinoma in the United States - Hu, Jia; Ye, Zhuomiao; Xu, Zhe; Hao, Zhinan; Wang, Yongjun (Frontiers in Public Health, 2022)
Background The national Comprehensive Cancer Network has suggested pembrolizumab as a second-line therapy for esophageal squamous cell carcinoma (ESCC) patients with a programmed death ligand-1 (PD-L1) combined positive score (CPS) ≥ 10. However, despite the increased survival rate associated with pembrolizumab in these patient population, the high cost of pembrolizumab may influence its antitumor effect. This study aimed to evaluate the cost-effectiveness of pembrolizumab compared to chemotherapy as second-line treatments for esophageal carcinoma (EC) based on KEYNOTE-181 trial. Methods A Markov model was constructed using TreeAge 2021 based on three different groups: all intent-to-treat patients (ITT population), patients with ESCC (ESCC population), and patients with a PD-L1 CPS ≥10 (CPS ≥10 population). Incremental cost, Incremental effect, Life-years, quality-adjusted life-years (QALYs) and incremental cost–effectiveness ratio (ICER) were calculated. Analyses were conducted on the setting of a willingness-to-pay threshold of $150,000 from the US perspective. Results The ICERs for pembrolizumab were $157,589.545 per QALY, $60,238.823 per QALY, and $100,114.929 per QALY compared with chemotherapy in the ITT, ESCC, and CPS≥10 populations, respectively. The ICER of the ITT population was higher than $150,000, suggesting that pembrolizumab was not a cost-effective treatment scheme in patients with a PD-L1 CPS ≤ 10 or esophageal adenocarcinoma. The ICER was < $150,000 in the ESCC and CPS≥10 populations, indicating that pembrolizumab was cost-effective in these two subgroups. Conclusion The determining of pembrolizumab as a cost-effective second-line therapy for EC in the United States depends on the histologic type and PD-L1 expression.